Monitoring of Virulence Factors and Metabolic Activity in Aggregatibacter Actinomycetemcomitans Cells Surviving Antimicrobial Photodynamic Therapy via Nano-Chitosan Encapsulated Indocyanine Green - Pourhajibagher, Maryam; Rokn, Amir Reza; Rostami-Rad, Mehdi; Barikani, Hamid Reza; Bahador, Abbas (Frontiers in Physics, 2018)
Aggregatibacter actinomycetemcomitans is an etiological agent frequently found in both chronic and aggressive periodontitis as well as peri-implantitis. This study assessed the effect of antimicrobial photodynamic therapy (aPDT), as an alternative treatment modality, by nano-chitosan encapsulated indocyanine green (CNPs/ICG), as a photosensitizer, on the virulence features of cell-surviving aPDT against A. actinomycetemcomitans. The cell cytotoxicity effect of CNPs/ICG was evaluated on primary human gingival fibroblast cells. A. actinomycetemcomitans ATCC 33384 photosensitized with CNPs/ICG was irradiated with diode laser at a wavelength of 810 nm for 1 min (31.2 J/cm2), and then bacterial viability measurements were done. The biofilm formation ability, metabolic activity, and antimicrobial susceptibility profiles were assessed for cell-surviving aPDT. The effect of aPDT on the expression of the fieF virulent gene, encoding the ferrous-iron efflux pump, was evaluated by the quantitative real-time PCR. CNPs/ICG-aPDT resulted in a significant reduction of cell viability (91%), biofilm formation capacity (53%), and metabolic activity (48%) of A. actinomycetemcomitans when compared to the control group (P < 0.05). Moreover, fieF gene expression was downregulated by 14.8 folds after the strains were treated with aPDT. The virulence of A. actinomycetemcomitans strain reduced in cells surviving aPDT with CNPs/ICG, indicating the potential implications of aPDT for the treatment of A. actinomycetemcomitans infections in periodontitis and peri-implantitis in vivo.